TWO EXTRACTION METHODS AND CLASSIFICATION OF THE SAPONIN OF THE SAPINDUS SAPONARIA L., “BOLICHE” - Tomás Ch., G. (2010)
We used the plant of “boliche” of the region of the northwest of Lima Sapindus Saponaria L. as a raw material for extraction, separation and classification of the saponin obtained. The extraction was performed by two different methods, in order to ascertain the most efficient. One method degrease the sample with chloroform and then extracts the saponin with ethanol in soxhlet, while the other method makes a maceration with ethanol. In both cases we obtain a crude extract of saponins, which is hydrolyzed to give brown crystals and by recrystallization reach transparent white color. Saponnins founded are classified as saponin triterpenes, more percentage of saponins in the method used chloroform for degrease.